Use of Autografts and Homografts in Keloid Surgery - S. P. Singla; Madan Lal; V. K. Puri; Sotantar Rai (Indian Journal of Plastic Surgery)
To evaluate the use of homografts in surgical treatment of keloids in comparison to the use of autografts in twenty-five patients the lesions have been excised intrakeloidally. Half of the resultant wound was covered with homograft and the other half with autograft. To eliminate individual variations of wound healing, the autografts and homografts have been used in the same patient. The results in respect of cure (32 percent in both groups) and recurrence rate (68 percent autograft, 64 percent homograft) are almost similar in both experimental and control wounds. It takes longer time (30-40 days) for wound healing with homograft as compared to (7-10 days) with autograft. Keloid formed in 5 (20 percent) patients at donor site of autograft. Use of homograft spared the patients from new keloid formation at donor sites.